(untitled) (Research, Society and Development, 2022)
The research aims to present the epidemiological profile and the main diseases that caused disability retirement in public servants of a federal university. This is a cross-sectional, retrospective study, whose target population was civil servants who needed to be retired due to disability at a federal university, from 2015 to 2019. The following variables were analyzed: age, gender, work capacity, position and cause of disability retirement. In the period studied, 16 servers needed to retire due to disability. Most were over 40 years old (N=14, 87.5%), occupied the positions of nursing assistant (N=5, 31.25%) and professor (N=5, 31.25%), located at the Health Campus (N =9, 56.25%). The main causes of disability retirement were mental and behavioral disorders (N=5, 31.25%), followed by neoplasms, diseases of the circulatory system and musculoskeletal and connective system, each with 3 disability retirements, representing 18.75% of them. . It was verified with this study that it is important to more carefully evaluate the working conditions of the employees of the Health Campus and the servers of the positions of nursing assistant and professor, in order to prevent illness and the need for disability retirement.